Load Frequency Control for Two Area Using Intelligent Control - Ali Adil Rafea, Arkan Ahmed Hussein (Mathematical Statistician and Engineering Applications, 2023)
The content of our study is to control the loading frequency of two regions using particle swarm optimization (PSO), genetic algorithms (GA), sine cosine algorithms(SCA) and relative integral derivative (PID) algorithms. Thetraditional PID controller is developed using the optimization algorithms we mentioned earlier and has reduced frequency change and has faster response. Integral Time Absolut Error (ITSE) is the function used in all algorithms for error calculation.The results showed that the algorithms had better results than the traditional method, and the SCA algorithm was also the best among them in terms of response speed.